Pemikiran Ulama Persatuan Tarbiyah Islamiyah (PERTI) Terhadap Polemik Maulid Nabi di Minangkabau - Diyanto, Rahman; Muhammad Yunus (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2024)
The dynamics of the early 20th century between the old and the young gave birth to a golden age for intellectuals. Several religious traditions that had previously taken root began to be questioned by young people, giving rise to works in the form of satire and apologetics. One of the religious traditions at issue is the Prophet's birthday. Young people who are gathered in Sumatra Thawalib, such as HAKA and Abdullah Ahmad, through their writings, say that the birthday tradition, in this case 'standing the birthday', is heresy. This was then responded to and refuted by the law of circumcision by the elderly who were gathered in the Islamic Tarbiyah Association (PERTI) through their writings. Based on this, this article wants to look at the thoughts of PERTI ulama in maintaining the sanctity of the law of Mawlid through the socio-religious dynamics that gave birth to apologetic works.